2009
DOI: 10.1523/jneurosci.0774-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Shapes Auditory Processing in the Adult Brain by Regulating Inhibitory Transmission and Plasticity-Associated Gene Expression

Abstract: Estradiol impacts a wide variety of brain processes, including sex differentiation, mood, and learning. Here we show that estradiol regulates auditory processing of acoustic signals in the vertebrate brain, more specifically in the caudomedial nidopallium (NCM), the songbird analog of the mammalian auditory association cortex. Multielectrode recordings coupled with local pharmacological manipulations in awake animals reveal that both exogenous and locally generated estradiol increase auditory-evoked activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
219
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(245 citation statements)
references
References 91 publications
(153 reference statements)
25
219
1
Order By: Relevance
“…Our results for the auditory midbrain parallel a number of studies from other taxa that describe an important role for estradiol in sensory processing of social signals and of audition (Arch and Narins, 2009;Caras, 2013;Earp and Maney, 2012;Maney, 2013;Maney et al, 2006Maney et al, , 2008Maney and Pinaud, 2011;Petrulis, 2013;Remage-Healey, 2012, 2014Sanford et al, 2010;Sisneros, 2009c;Tremere et al, 2009;Walpurger et al, 2004;Yovanof and Feng, 1983). In the túngara frog, a previous study showed that hCG, which stimulates production of gonadal steroids (Lynch et al, 2006;Wu et al, 2001), increases egr-1 expression in the laminar nucleus of the torus (Lynch and Wilczynski, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Our results for the auditory midbrain parallel a number of studies from other taxa that describe an important role for estradiol in sensory processing of social signals and of audition (Arch and Narins, 2009;Caras, 2013;Earp and Maney, 2012;Maney, 2013;Maney et al, 2006Maney et al, , 2008Maney and Pinaud, 2011;Petrulis, 2013;Remage-Healey, 2012, 2014Sanford et al, 2010;Sisneros, 2009c;Tremere et al, 2009;Walpurger et al, 2004;Yovanof and Feng, 1983). In the túngara frog, a previous study showed that hCG, which stimulates production of gonadal steroids (Lynch et al, 2006;Wu et al, 2001), increases egr-1 expression in the laminar nucleus of the torus (Lynch and Wilczynski, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…Future intracellular approaches will shed light on how estrogens acutely impact firing modes via possible neuronal membrane effects in NCM. (During manuscript preparation a study was published reporting that estrogen manipulation in NCM changes auditory multiunit activity and gene expression [21]. )…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the recent discovery that gravid females display stronger behavioral responses to olfactory-auditory conspecific males signals than nonreproductive females (Kasurak et al, 2012) and highlights a potential link between auditory function and reproductive behavior in female round goby. While the relationships between E2 and hearing measurements are associative rather than due to an experimental manipulation, physiological actions of steroids on the response properties of neurons are well known (Zakon, 1998) and there is increasing evidence for a stimulatory role of E2 in auditory function (Sisneros et al, 2004;Miranda and Wilczyinski, 2009;Tremere et al, 2009;Maruska et al, 2012). E2 could affect the number and kinetics of hair cell ion channels (Zakon, 1998), which could influence the frequency filtering properties of the auditory system, as activation and deactivation rates of ion channels are the main determinants of hair cell resonance (Fettiplace and Fuchs, 1999).…”
Section: Female Reproductive Conditionmentioning
confidence: 99%